Are race-specific ERCC1 haplotypes in melanoma cases versus controls related to the predictive and prognostic value of ERCC1 N118N?. Issue 1 (3rd January 2013) - Gao, Rui; Reece, Kelie M; Sissung, Tristan; Fu, Samuel H; Venzon, David J; Reed, Eddie; Spencer, Shawn D; Price, Douglas K; Figg, William D
Abstract : Objectives: Although it does not alter the ERCC1 phenotype, the ERCC1 500C>T (rs11615) polymorphism has undergone a myriad of investigations into its role as a marker for nucleotide excision repair (NER) function in different races, diseases and treatment outcomes. The goal of our study was to test the hypothesis that 500C>T is in linkage disequilibrium (LD) with causative alleles, and that these haplotypes are more frequent in Caucasians with melanoma than in healthy Caucasians or African Americans. Design: In this case–control study, we selected race-specific ERCC1 single-nucleotide polymorphism (SNPs), conducted LD analysis with ERCC1 500C>T and compared the frequency of ERCC1 diplotypes in Caucasians with melanoma (n=165), healthy Caucasians (n=150) and healthy African Americans (n=159). The haplotype was further studied using a fusion gene containing multiple ERCC1 SNPs. Setting: Large cancer institute in the USA. Participants: A total of 165 Caucasian melanoma patients, 159 healthy Caucasian controls and 159 African American healthy controls. Men and women were enrolled in the clinical trial; however, since the screening trial included prostate cancer screening in addition to screening for other cancers, only male controls were available. Outcome measures: The outcome measures were melanoma risk in Caucasians, and LD between ERCC1 SNP, N118N and other race-specific allelic variants. Results: When compared to ERCC1 500C>T alone, a race-specific three-SNP variant haplotype in ERCC1 (comprised of rs11615, rs3212950 and rs3212948) was even more frequent in Caucasians with melanoma than in healthy Caucasians (p=0.0034) or African Americans (p<0.0001). A plasmid containing the variant haplotype was not differentially expressed. Conclusions: We demonstrate that ERCC1 500C>T participates in a previously characterised cancer-risk haplotype found more frequently in Caucasians, while LD is weak in African Americans; this haplotype appears to also be related to melanoma. It is therefore likely that ERCC1 500C>T is only a valid NER, disease or treatment outcome marker in Caucasians.